Salud mental a nivel familiar desde la perspectiva de Alteridad (2011)
This article develops an approach to the different dimensions which relate family health topic to alterity. To do this, it involves several authors who have supported the theoretical framework of altered alterity, as pathology in the family, and the healthy alterity or encounter in the family group. At the end, it analyzes ways to give a new answer orienting this reality and its repercussions in the health of family systems.